The iMovie '11 project book : stuff you can do with iMovie - Carlson, Jeff (Peachpit Press, 2011)
Provides information on the features of iMovie '11, describing such topics as editing video and audio, adding effects, organizing a video library, making a music video, and posting finished films to YouTube and Facebook.